Boganmeldelser - Rynning, Elisabeth; Gottlieb, Peter; Ericsson, Kjersti; Gregersen, M.; Dünkel, Frieder; Andersen, Heidi Mork; Ljungstrøm, Alexander Carnera; Skjørsten, Kristin (Nordisk Tidsskrift for Kriminalvidenskab, 1992)
Book reviews